Photovoltaic solar farm; earthing system design for cost reduction and system compliance - Mohamad Nassereddine; Khaled Ali; Chadi Nohra (Institute of Advanced Engineering and Science, 2020)
The increasing demand for green sustainable energy source led to a worldwide increase in the installation of large scale photovoltaic (PV) farms. To ensure the PV farms compliance with safety and operational guidelines, earthing systems are essential component of the design. An adequate earthing system for low, medium, and high voltage areas of the PV farm ensures energy under fault condition and system malfunction are absorbed without exceeding the desirable limits. The work in this paper captures the soil resistivity and the earthing system requirements for each voltage level. The paper highlights the boundaries for combined or separate earthing system between low, medium and high voltage. Furthermore, the works focus on the system cost and maintenance without jeopardizing system integrities and safety compliance. Case study is also included.